2020
DOI: 10.1038/s41598-020-64534-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to kinase inhibition in FGFR2-addicted triple negative breast cancer cells: a quantitative phosphoproteomics study

Abstract: Although these two triple-negative FGFR2-overexpressing cell lines both display an addiction to FGFR2 activation, it is apparent that the proteomic landscapes differ, which may impact on their global response to inhibitor treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 132 publications
(163 reference statements)
0
9
0
Order By: Relevance
“…Strikingly, the AAMDC KD induced enlarged LAMP2 + late endosomal vesicles, which exhibited a degree of positive staining for p-mTOR S2448 (Supplementary Fig. 3b ) and fibroblast growth factor receptor 2 (FGFR2), which is overexpressed in IntClust2 SUM52PE cells and confers activation of PI3K 20 (Supplementary Fig. 7b ).…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, the AAMDC KD induced enlarged LAMP2 + late endosomal vesicles, which exhibited a degree of positive staining for p-mTOR S2448 (Supplementary Fig. 3b ) and fibroblast growth factor receptor 2 (FGFR2), which is overexpressed in IntClust2 SUM52PE cells and confers activation of PI3K 20 (Supplementary Fig. 7b ).…”
Section: Resultsmentioning
confidence: 99%
“…The MAPK pathway, including ERK1/2, JNK and p38 kinases [ 16 18 ], regulates transcription [ 19 ] and recruits negative signalling regulators like the E3 ligase CBL, the adaptor SPROUTY and the phosphatase SHP2 [ 20 , 21 ]. By contrast, AKT induces the activation of the mTOR complex 1 [ 22 ] and the phosphorylation of the FOXO1 transcription factor [ 23 ] ( figure 2 c ). Following recruitment to activated FGFR the enzyme PLCγ induces calcium ion release, resulting in the activation of downstream kinases like PKC [ 24 ] ( figure 2 c ).…”
Section: Overview Of Fgfr Signallingmentioning
confidence: 99%
“…The FGFR2 gene is located on the 10q26.13 chromosomal region, which is amplified in only 5% of all breast cancer patients, in particular TNBC patients [ 199 ]. In TNBC, FGFR2 amplification has been associated with robust activation of signalling, cellular transformation and resistance to FGFR inhibitors in pre-clinical models [ 3 , 22 , 103 , 200 ]. However, very recently it has been reported that FGFR2 can be expressed also in ER/PR-positive tumours where, surprisingly, low FGFR2 expression correlates with poor prognosis [ 201 ] ( figure 4 ).…”
Section: Fgfrs In Breast Cancermentioning
confidence: 99%
“…It has become increasingly appreciated that the mechanisms underpinning adaptive resistance can be highly heterogeneous and context-specific, even in response to the same drug compounds (45). This is primarily driven by variation in protein expression and/or mutational profiles observed across and within different cancer cell types, resulting in context-specific differences in feedback and crosstalk strengths that impact on drug response (19,28).…”
Section: Discussionmentioning
confidence: 99%